2011
DOI: 10.1097/mao.0b013e3182267f02
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict the Efficacy of the Semont Maneuver in the Treatment of Benign Paroxysmal Positional Vertigo of the Posterior Semicircular Canal?

Abstract: The presence of orthotropic nystagmus in the second position of the Semont maneuver indicates a good prognosis, but its absence does not necessarily mean that the maneuver will fail. Orthotropic nystagmus is more common in patients with shorter latency periods, suggesting that its appearance is related to cupulolithiasis mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 16 publications
2
27
0
1
Order By: Relevance
“…Despite the well-known phenomenon of fatigue that can mimic successful treatment due to dispersion of particles in the canal after repeated positional maneuvers [7], we did not find any statistically significant differences between the 1 and the 24 h follow-ups. We confirmed the utility of the so-called 'liberatory nystagmus' [6,8] as a prognostic factor for efficacy of treatment in most cases; nevertheless, its absence does not necessarily mean that the maneuver will be unsuccessful [8]. More than one maneuver was needed to treat the PC-BPPV in 15% of subjects.…”
Section: Discussionsupporting
confidence: 75%
“…Despite the well-known phenomenon of fatigue that can mimic successful treatment due to dispersion of particles in the canal after repeated positional maneuvers [7], we did not find any statistically significant differences between the 1 and the 24 h follow-ups. We confirmed the utility of the so-called 'liberatory nystagmus' [6,8] as a prognostic factor for efficacy of treatment in most cases; nevertheless, its absence does not necessarily mean that the maneuver will be unsuccessful [8]. More than one maneuver was needed to treat the PC-BPPV in 15% of subjects.…”
Section: Discussionsupporting
confidence: 75%
“…Authors such as Oh et al [5] and Soto-Varela et al [6] have reported the need to be attentive to the presence of a nystagmus with the same characteristics as that observed in the diagnostic tests: 'orthotropic nystagmus.' This finding could be associated with a better prognosis after repositioning maneuvers as it indicates that particles are moving in the ampullofugal direction during the corresponding CRM.…”
Section: Discussionmentioning
confidence: 94%
“…The presence of a nystagmus observed throughout the different positions of the maneuver, with the same fast phase direction as detected during the first position [5,6], i.e. ON, was registered and characterized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most widely accepted theories aiming to explain this phenomenon is the canalithiasis theory, which states that otoconial debris are freely floating in the endolymph of the semicircular canal [Parnes and McClure, 1992], and the cupulolithiasis theory, in which the particles are at least partly adhered to the cupula of the ampullar end of the canal [Schuknecht, 1969]. For the last few years, BPPV treatment has been based on particlerepositioning maneuvers or canalith repositioning procedures (CRPs) that aim at removing otoconial debris from the semicircular canal and returning them to the vestibule [Soto-Varela et al, 2011].…”
Section: Introductionmentioning
confidence: 99%